Myeloperoxidase-antineutrophil cytoplasmic antibody-associated diffuse alveolar hemorrhage caused by denosumab. (2022) - Kasemchaiyanun, Akarawut; Boonsarngsuk, Viboon; Liamsombut, Somprasong; Incharoen, Pimpin; Sukkasem, Warawut
Abstract: Denosumab is a bone anti-resorptive drug, commonly used for treating osteoporosis. Pulmonary involvement has rarely been reported as a possible serious adverse effect of this medication. Herein, we report the case of a 67-year-old woman who presented with non-massive hemoptysis, anemia, and extensive pulmonary opacities on a chest radiograph for 3 days after receiving denosumab. The patient was diagnosed with myeloperoxidase-antineutrophil cytoplasmic antibody-associated pulmonary hemorrhage secondary from denosumab. She was treated with high doses of intravenous methylprednisolone and cyclophosphamide combined with plasmapheresis. Subsequently, her clinical and radiological findings improved without residual abnormalities after treatment.